The Tourists: A campaign - Vorgia, Pasqua; Babasikas, Petros (Design/Arts/Culture, 2024)
"The Tourists" is a subversive tourism campaign by the Depression Era collective, reflecting on the simultaneous influx of refugees and global tourism in Southern Europe. Through diverse media, it exposes landscapes marked by hidden violence, portrays individuals in states of flux, and blurs the line between idyllic tourism and harsh reality.